Springate, Ohlson, Altman Z-Score, Zmijewski, Grover, CA Score Model of Financial Distress Analysis in Retail Companies - Tiana Putri, Inggit; Hadiwibowo, Imam; Taufik Azis, Mohammad (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
This study aims to analyze the predictions of the Springate, Ohlson, Altman Z-Score, Zmijewski, Grover, and CA-Score models for retail sector companies listed on the IDX for the 2019-2022 period for financial distress. In this study, a sample of 20 companies in the retail sector was used for the 2019-2022 period using 80 financial reports. The research sample was determined by purposive sampling technique. The data used in this research is secondary data. The data analysis method used is quantitative data analysis. The conclusion of this study is that the most accurate and suitable model for predicting financial distress in retail companies listed on the IDX in the 2019-2022 period is the Grover model. Keywords: Springate, Ohlson, Altman Z-Score, Zmijewski, Grover, CA-Score